2013
DOI: 10.1210/en.2012-2162
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Brown Adipose Tissue, or Beige Fat, Is Anabolic for the Skeleton

Abstract: It is known that insulin resistance and type 2 diabetes mellitus are associated with increased fractures and that brown adipose tissue (BAT) counteracts many if not all of the symptoms associated with type 2 diabetes. By the use of FoxC2(AD)(+/Tg) mice, a well-established model for induction of BAT, or beige fat, we present data extending the beneficial action of beige fat to also include a positive effect on bone. FoxC2(AD)(+/Tg) mice are lean and insulin-sensitive and have high bone mass due to increased bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 51 publications
2
93
0
Order By: Relevance
“…Irisin is known to activate the browning response in WAT, when injected daily at a dose of 500 μg kg −1 for 14 d (19,20). We therefore chose a substantially lower dose of r-irisin (100 μg kg −1 , weekly injections) to determine whether or not the skeletal action of irisin was dependent on the expansion of inducible BAT (iBAT).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Irisin is known to activate the browning response in WAT, when injected daily at a dose of 500 μg kg −1 for 14 d (19,20). We therefore chose a substantially lower dose of r-irisin (100 μg kg −1 , weekly injections) to determine whether or not the skeletal action of irisin was dependent on the expansion of inducible BAT (iBAT).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, at a dose of 500 μg kg −1 daily (3,500 μg kg −1 per week), r-irisin increased Ucp1 expression and reduced body weight. However, because BAT, particularly iBAT, can be beneficial to the skeleton (20,48,49), it was imperative that we exclude indirect effects of irisin on the skeleton exerted through iBAT. We therefore used a 35-fold lower cumulative weekly dose of r-irisin than that used previously to induce browning (19).…”
Section: Discussionmentioning
confidence: 99%
“…10 During the same time, it has been reported that this inducible form of brown adipose (iBAT) is anabolic for the skeleton. 37 Studies on transgenic mice overexpressing FoxC2 in the adipose tissue, a well-established model for BAT induction, showed that these mice displayed a higher trabecular bone mass, as compared with age-matched WT animals, due to increased bone formation, triggered by Wnt10b and IGFBP2, two pivotal bone anabolic molecules released from BAT. 37 Another work by Zhang et al 38 demonstrated that therapeutic treatment of normal and obese mice with r-Irisin at a dose of 3500 mg kg À 1 per week strongly induced the browning…”
Section: A Possible Combined Direct and Indirect Effect Of Irisin On mentioning
confidence: 99%
“…4 The induction of the presumably beige adipocytes is accompanied by protection against obesity and diet-induced insulin resistance in response to a high-fat diet. 4,42 Using this mouse strain as a model for increased 'BAT content', Rahman et al 43 recently showed that these mice have significantly higher trabecular bone mass, due to increased bone formation associated with high bone turnover, as compared with wild-type mice, suggesting that BAT is anabolic for the skeleton. Interestingly, the authors also shed some light on a potential mechanism by which BAT stimulates this effect.…”
Section: The Connection Between Bat and Bonementioning
confidence: 99%